2007
DOI: 10.1016/j.cell.2006.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of Cognate SNAREpins by Sec1/Munc18 Proteins

Abstract: Sec1/Munc18 (SM) proteins are required for every step of intracellular membrane fusion, but their molecular mechanism of action has been unclear. In this work, we demonstrate a fundamental role of the SM protein: to act as a stimulatory subunit of its cognate SNARE fusion machinery. In a reconstituted system, mammalian SNARE pairs assemble between bilayers to drive a basal fusion reaction. Munc18-1/nSec1, a synaptic SM protein required for neurotransmitter release, strongly accelerates this reaction through di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
770
5
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 436 publications
(850 citation statements)
references
References 69 publications
61
770
5
14
Order By: Relevance
“…In all systems to date, over expression of the appropriate Munc18 protein isoform was found to inhibit membrane vesicle fusion, suggesting that this protein function as a fusogenic inhibitor [48,[53][54][55][56]. Structural studies indicated that the Munc18 proteins induces a closed conformational state of syntaxin thereby rendering it unable to bind to VAMP or SNAP consistent with in vitro binding assays [57,58]. However, genetic studies in yeast, worms, flies and in the mammalian nervous system have also found that the loss of Munc18 expression also prevents vesicle fusion suggesting that Munc18 proteins play a required positive fusogenic role [56,59].…”
Section: Glut4 Vesicle Docking and Plasma Membrane Fusionmentioning
confidence: 86%
See 1 more Smart Citation
“…In all systems to date, over expression of the appropriate Munc18 protein isoform was found to inhibit membrane vesicle fusion, suggesting that this protein function as a fusogenic inhibitor [48,[53][54][55][56]. Structural studies indicated that the Munc18 proteins induces a closed conformational state of syntaxin thereby rendering it unable to bind to VAMP or SNAP consistent with in vitro binding assays [57,58]. However, genetic studies in yeast, worms, flies and in the mammalian nervous system have also found that the loss of Munc18 expression also prevents vesicle fusion suggesting that Munc18 proteins play a required positive fusogenic role [56,59].…”
Section: Glut4 Vesicle Docking and Plasma Membrane Fusionmentioning
confidence: 86%
“…However, genetic studies in yeast, worms, flies and in the mammalian nervous system have also found that the loss of Munc18 expression also prevents vesicle fusion suggesting that Munc18 proteins play a required positive fusogenic role [56,59]. In this regard, recent in vitro studies have suggested that the Munc18 proteins function to anchor VAMP to syntaxin thereby promoting fusion if added during the fusion reaction [58].…”
Section: Glut4 Vesicle Docking and Plasma Membrane Fusionmentioning
confidence: 99%
“…However, this antibody cannot recognize Munc18-bound syntaxin 1, probably owing to occlusion of the binding epitope (Rickman & Davletov, 2005). Two recent studies indicated that exogenously added, recombinant GST-Munc18 binds to assembled SNARE complexes (Latham et al, 2007;Shen et al, 2007). As the existence of a native mammalian Munc18-SNARE association has not been shown, we investigated native Munc18 interactions using two alternative immunopreparative chromatographies.…”
Section: Resultsmentioning
confidence: 99%
“…After arachidonic acid action, continued association of Munc18 with assembled syntaxin-SNAP25 is consistent with the crucial role of Munc18 in downstream vesicle docking and fusion. It was found that addition of recombinant Munc18 to partly assembled SNAREs upregulates liposomal fusion (Shen et al, 2007), but it is known that syntaxins partner with Munc18 even during transport to membrane destinations-that is, ab initio. Whereas Shen et al (2007) coexpressed syntaxin and SNAP-25 in the absence of Munc18 in bacteria, obtaining a preformed SNARE intermediate, our data indicate that a dynamic transition can be made from 'closed' syntaxin-Munc18 into an active SNAP25-bound configuration without loss of Munc18.…”
Section: Arachidonic Acid Activation Of Syntaxin-munc18 E Connell Et Almentioning
confidence: 99%
“…96 It also seems important for determining which SNARE protein isoforms interact, specifically ensuring interactions with syntaxin 1A/synaptobrevin 2. 100 In other systems, nSec1 promotes SNARE complex formation 102 showing that it may have additional regulatory functions not yet explored. Additionally, it has been shown to transport syntaxin 1A from the golgi to the cell surface in epithelial cells 103 and CHO cells 104 which indicates it may have a similar role in neurons.…”
Section: Functional Interactions Of Presynaptic Calcium Channels Withmentioning
confidence: 99%